Vicarious control and quality of life benefits in cancer patients. - Wesso-Rule, Nadia (My University, 2011)
Cancer patients often experience psychological distress during and after treatment. Studies have indicated that heightened distress in cancer patients and how they perceive this distress is associated with a number of negative outcomes that include poorer adherence to treatment and poorer quality of life (Skärstein, Aass & Fossa, 2000). Furthermore, studies have suggested that the type of health locus of control orientation individuals have may be linked to managing depression, anxiety and stress (Helgelson, 1992). This study, therefore, aimed to investigate whether a vicarious health locus of control predicted higher mental health quality of life and lower depression, anxiety and stress. In addition, previous studies indicated that health locus of control has a complex relationship with coping. Therefore, a further aim of this study was to determine whether coping moderated the relationship between vicarious control and each of mental health quality of life, depression, anxiety and stress. Participants were invited through internet social networking sites as well as independent cancer support groups to participate in the study, which required them to fill out five questionnaires. Multivariate analyses were conducted and results indicated that an increased vicarious locus of control was associated with increased mental health quality of life and lower depression. In addition, emotion-focused coping was suggested to be a significant moderator between a vicarious locus of control orientation and anxiety and stress